2016
DOI: 10.1016/j.juro.2016.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Stones: American Urological Association/Endourological Society Guideline, PART I

Abstract: Proper treatment selection, which is directed by patient- and stone-specific factors, remains the greatest predictor of successful treatment outcomes. This Guideline is intended for use in conjunction with the individual patient's treatment goals. In all cases, patient preferences and personal goals should be considered when choosing a management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
683
2
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(719 citation statements)
references
References 30 publications
6
683
2
28
Order By: Relevance
“…Counterbalancing for URS's higher SFRs, SWL is associated with the least morbidity and lower complication rates [65][66][67]. In this current systematic review, Clavien-Dindo grade complications were, if reported, less frequent in patients treated with SWL.…”
Section: Implications For Clinical Practicementioning
confidence: 59%
See 2 more Smart Citations
“…Counterbalancing for URS's higher SFRs, SWL is associated with the least morbidity and lower complication rates [65][66][67]. In this current systematic review, Clavien-Dindo grade complications were, if reported, less frequent in patients treated with SWL.…”
Section: Implications For Clinical Practicementioning
confidence: 59%
“…However, for stones >10 mm, SFR were comparable for URS and SWL (74% vs 79%) in the proximal ureter [64]. The current, 2016 American Urological Association Guidelines state that URS for proximal ureteral stones has a greater SFR in a single procedure compared with SWL, regardless of stone size [65,66], albeit the importance of informing patients on the higher morbidity and complications risk compared with SWL. All in all, URS can be recommended as the first treatment option for proximal ureteral stones >10 mm, but for stones 10 mm the EAU Urolithiasis Guidelines panel consensus is that either treatment options are viable as first choice and should be presented to patients [67].…”
Section: Implications For Clinical Practicementioning
confidence: 96%
See 1 more Smart Citation
“…Both European Urology Association and American Urological Association guidelines recommend PCNL as the treatment option for larger renal calculi [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao controlo imagiológico pós-operatório, registámos o tempo até este, qual o tipo de exame utilizado e a presença ou ausência de litíase residual superior a 3 mm. 7,8 No caso de falência, avaliada pelo controlo imagiológico, registámos a abordagem adotada posteriormente em termos de terapêutica (Fig.1).…”
Section: Introductionunclassified